Value-Based Healthcare Project Implementation in a Hierarchical Tertiary Hospital: Lessons Learned - Varela-Rodríguez, Carolina; García-Casanovas, Albert; Baselga-Penalva, Blanca; Ruiz-López, Pedro M. (Frontiers in Public Health, 2022)
Currently, the main innovation in healthcare is the value-based healthcare (VBHC) framework, supposedly a way to solve health services' sustainability problem and ensure continuous improvement of healthcare quality. The Quality and Safety Unit at the Hospital Universitario 12 de Octubre has been since May 2018 coordinating the implementation of several healthcare innovation projects within the paradigm of VBHC. Implementing innovations in a complex institution, such as a tertiary hospital, is a challenge; we present here the ten lessons learned in the last four years of work. We detail exclusively the aspects related to continuous improvement and value addition to the process. In summary, for any VBHC project implementation, we found that there are five main issues: 1) adequate data quality; 2) development of data recording and visualization tools; 3) minimizing healthcare professional's effort to record data; 4) centralize governance, coordination, and transparency policies; 5) managerial implication and follow-up. Following, we describe six steps key ensuring a successful implementation: testing the feasibility and complexities of the entry process; establishing leadership and coordination of the project; developing patient-reported outcomes and experience measurements; developing and adapting the data recording and data analysis tools; piloting in the medical condition, and evaluating the results and project management. The implementation duration can vary depending on the complexity of the Medical Condition Clinical Process and Patient Pathways. However, we estimate that the implementing phase will last a minimum of 12 and a maximum of 24 months. During this period, the institution should be capable of designing and implementing the proposed innovations. The implementation costs vary as well depending on the complexity ranged from 90.000 euros to 250.000 euros. Implementation problems included the resistance to change of institutions and professionals. In fact, up to date, there are few successful implementations of operative value-based healthcare. Our quality of care and patient safety methodological approach to the implementation seems to give a particular advantage.